2013
DOI: 10.7883/yoken.66.51
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Epidemiology of Clinically Isolated Cryptococcus neoformans Strains in Japan by Multilocus Sequence Typing

Abstract: SUMMARY:Cryptococcus neoformans and Cryptococcus gattii are the causative agents of cryptococcosis. Despite its importance, our knowledge of the epidemiology of cryptococcosis in Japan remains limited. To establish an epidemiological database on cryptococcosis in Japan, we determined the genetic variability of 44 Japanese clinical isolates of C. neoformans (var. grubii: serotype A) by multilocus sequence typing (MLST). The strains were clinically isolated from 1992 to 2011 in 5 different areas of Japan (the Ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 15 publications
2
15
0
Order By: Relevance
“…neoformans and C . gattii , favoring data comparison and overcoming problems arising from inter-laboratory reproducibility [ 45 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…neoformans and C . gattii , favoring data comparison and overcoming problems arising from inter-laboratory reproducibility [ 45 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, MLST analyses of several hundred VNI isolates from the United States and a dozen other countries yielded only a few distinct genotypes (designated M1 to M5), of which genotype M5 was the most prevalent (18,20). Subsequent investigations have shown that the M5 is the dominant genotype among clinical isolates from China, Japan, Thailand, and South Korea (34)(35)(36)(37). In contrast to the limited genetic diversity observed among global isolates of VNI, two subpopulations of VNI coexist in southern Africa: (i) strains with SA VNI genotypes that are closely related to the global genotypes of VNI (see Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, data obtained from previous studies of 30 C. neoformans var. grubii isolates (11 VNB, 10 VNI, and 9 VNII) were included in the analysis as outgroup strains (Khayhan et al, 2013; Litvintseva et al, 2006; Sanchini et al, 2014; Cogliati et al, 2013; Meyer et al, 2009; Kaocharoen et al, 2013; Choi et al, 2010; Umeyama et al, 2013; Wiesner et al, 2012) (Table S1). …”
Section: Methodsmentioning
confidence: 99%